2017
DOI: 10.1021/acs.jced.7b00012
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Solubility of Nifedipine and Quinine in Supercritical Fluid Carbon Dioxide Using Continuously Stirred Static Solubility Apparatus Interfaced with Online Supercritical Fluid Chromatography

Abstract: A high pressure vessel equipped with continuous magnetic stirring has been interfaced directly online with supercritical fluid chromatography (SFC). The interface consists of an oven housing a recirculation pump that maintains a constant flow of supercritical fluid solution from the vessel through a sample injection valve for online SFC analysis. The method involves increasing the vessel pressure in controlled steps to produce a series of progressively more saturated supercritical fluid carbon dioxide solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Although some compounds rapidly reach equilibrium, it has been demonstrated that 3−12 h stirring may be necessary for some compounds before solubility measurements can be reliably performed. 8,10,27 According to the findings of this study, chloramphenicol provides a slow dissolution rate in SF-CO 2 . This can be rationalized due to its high polarity especially with the contribution made by the N-oxide resonance structure shown in Figure 1.…”
Section: Comparison Of Ssv−sfc Chloramphenicol Solubility Results Onl...mentioning
confidence: 68%
See 3 more Smart Citations
“…Although some compounds rapidly reach equilibrium, it has been demonstrated that 3−12 h stirring may be necessary for some compounds before solubility measurements can be reliably performed. 8,10,27 According to the findings of this study, chloramphenicol provides a slow dissolution rate in SF-CO 2 . This can be rationalized due to its high polarity especially with the contribution made by the N-oxide resonance structure shown in Figure 1.…”
Section: Comparison Of Ssv−sfc Chloramphenicol Solubility Results Onl...mentioning
confidence: 68%
“…As previously reported, significant differences in published SF-CO 2 solubility data for the same compound is a common occurrence and the various factors that might give rise to this situation have been cited. 8,9,20 In situ checking procedures to ensure solubility measurements are performed at fully established equilibrium dissolution using the relevant system mixing conditions are vital to obtain reliable results. Although some compounds rapidly reach equilibrium, it has been demonstrated that 3−12 h stirring may be necessary for some compounds before solubility measurements can be reliably performed.…”
Section: Comparison Of Ssv−sfc Chloramphenicol Solubility Results Onl...mentioning
confidence: 99%
See 2 more Smart Citations
“…We have earlier [ 31 ] proposed a static approach to sorption analysis in SC media based on on-line supercritical fluid chromatography (SFC). A similar approach was applied in several works to determine the substance solubility in SCF [ 32 , 33 , 34 , 35 ] and distribution coefficients in the liquid-SCF system [ 36 , 37 , 38 , 39 , 40 ], and to control chemical reactions [ 41 , 42 ]. It allows fast quantitative analysis of the considered system components without depressurization or special sample preparation.…”
Section: Introductionmentioning
confidence: 99%